1962
DOI: 10.1111/j.1755-3768.1962.tb07835.x
|View full text |Cite
|
Sign up to set email alerts
|

Waardenburg's Syndrome in Father and Daughter

Abstract: In 1950-51, Waardenburg (15,16,17) showed that some well-known developmental anomalies in the interocular region associated with deafness and certain pigmentary defects constitute a syndrome which is inherited as a dominant character. The syndrome consists of the following features: lateroverse dystopia of the medial canthi (estimated penetrance, 99 O/O), prominent nose root (78 O / o ) , hyperblasia of the medial part of the eyebrows with frequent overgrowth (synophrys) (45 O/O), heterochromia iridum (25 O/O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

1965
1965
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
0
2
0
3
Order By: Relevance
“…In the antecedent 20 years, a myriad of studies (Arias, 1971; Hageman and Delleman, 1977) have apportioned Waardenburg syndrome (WS) into several forms, based on whether dystopia canthorum is present (type I) or absent (type II), and whether upper limb defects present (type III, Klein-Waardenburg syndrome) (Klein, 1983) or associated with Hirschsprung disease (type IV, Waardenburg Shah (1981). Waardenburg syndrome types I, II, and III demonstrate the autosomal dominant type of inheritance with an imperative complete penetrance and variable expression (Lalwani, 1996; Thorkilgaard, 1962). Dystopia canthorum which is defined as a prominent broad nasal root with increased intercanthal distance is the most penetrated feature of WS and is found in 41.2%–99% of the reported cases (Choi et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the antecedent 20 years, a myriad of studies (Arias, 1971; Hageman and Delleman, 1977) have apportioned Waardenburg syndrome (WS) into several forms, based on whether dystopia canthorum is present (type I) or absent (type II), and whether upper limb defects present (type III, Klein-Waardenburg syndrome) (Klein, 1983) or associated with Hirschsprung disease (type IV, Waardenburg Shah (1981). Waardenburg syndrome types I, II, and III demonstrate the autosomal dominant type of inheritance with an imperative complete penetrance and variable expression (Lalwani, 1996; Thorkilgaard, 1962). Dystopia canthorum which is defined as a prominent broad nasal root with increased intercanthal distance is the most penetrated feature of WS and is found in 41.2%–99% of the reported cases (Choi et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Hageman suggested that vestibular dysfunction should not be considered as an essential symptom in WS [7]. Thorkilgaard et al also reported normal vestibular functions in WS patients [19]. Therefore it is still unclear whether the abnormal vestibular function should be considered as one of the characteristic features in WS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Αϊ δημοσιεύσεις των ήγειραν παγκόσμιον ενδιαφέ ρον διά τήν ελάχιστα μέχρι τότε γνωστήν συνδρομήν. Ήκολούθησαν πολλαί ανακοινώσεις περιπτώσεων της συνδρομής επί ατόμων διαφόρων εθνικοτήτων, δπως Βρετανών 31,73 , Βέλγων 25 , 'Ισραηλιτών , 'Ινδών °' 34 , εγχρώμων του 'Ακρωτηρίου (Cape Colored) 24 ' 60 , Δανών 86 , φυλής Bantu 80 , Ισπανών 91 , Νορβηγών 1 , Ζουλού 14 , 'Ιαπώνων 69,84 , Καναδών 74 , Μαορί 43 , Γερμανών 2 , Νέγρων 13,35,36,41,57,75 , Γάλλων 12 , 'Ολλανδών ' , 'Αμερικανών 29,77 , Γιουγκοσλάβων 66 , 'Ιταλών 32,89 ,…”
Section: πίναξunclassified
“…Ή μία ϊρις δύναται νά είναι έξ ολοκλήρου κυανή καί ή άλλη εξ ολοκλήρου κεχρωσμένη, π.χ. καστανή (ολική ή πλήρης έτεροχρωμία) 93 , ή άμφότεραι δύναται νά έχουν έξ ολοκλήρου χαρακτηριστικόν ώχροκύανον χρώμα (ίσοϋποχρωμία) 26 , ή τις θεωρείται σήμερον επίσης ως μέρος της συνδρομής 23 ' 78 ' 86 . Ουχί άσυνήθως, ή κυανή ϊρις παρουσιάζει ποικίλου μεγέθους κεχρωσμένα τμήματα 26,93 (μερική έτεροχρωμία ή δίχρωμος ϊρις).…”
Section: κλινικη εικωνunclassified
See 1 more Smart Citation